Tourism Footprints On Society: Young Goan Women Speak Out - Kimberley , Severina Dias; Steffi , Maria Cardoz (2016)
Goa, is a small State situated on the western coast of India. The geography of Goa, with its indented coastline, beautiful beaches fringed with palm trees make it an attractive holiday destination. Further the history of Goa as a Portuguese colony right up till 1961, has left traces of a cultural heritage different from the rest of India. The food, music, dress and the physical presence of numerous churches and crosses around Goa which seem to a visitor as being western, has for the people of Goa been an imposition during the Portuguese regime. Since the 1990’s there has been a growing colonization of a different kind. Tourism was declared by the Government of Goa as an ‘Industry’ and that resulted in its booming growth. Goa which measures only a 100 kms from North to South has become a popular tourist destination attracting 5,41,480 foreign tourists, 47,56,422 domestic tourists in the last year (2015) totalling to 52,97,902 people in one year. The resident population in the State is 14,58,545 (Census 2011). The tourist population is 3 times more than that of the resident population. The impacts on the local population, local resources of food, water and space, as well as the environment degradation with large scale construction, sewage overload and garbage generated are only the tip of the iceberg. This paper discusses some of the concerns for sustainable development based on the impacts of tourism on local society and looks particularly at the impacts for young women from the voices of young women residing in Goa. Tourism is seen as a new colonizer. The paper will highlight some concerns namely drugs, alcohol consumption, growing casinos, non-availability of desired jobs, prostitution, paedophilia, rising incidence of violence against women.The authors of this paper are students of the M. A Programme in Women’s Studies at Goa University, Goa. This paper is an outcome of a study done amongst women students in Goa, India.